Hostname: page-component-745bb68f8f-hvd4g Total loading time: 0 Render date: 2025-02-06T17:14:00.677Z Has data issue: false hasContentIssue false

A $\boldsymbol {q}$-SUPERCONGRUENCE MODULO THE THIRD POWER OF A CYCLOTOMIC POLYNOMIAL

Published online by Cambridge University Press:  18 July 2022

CHUANAN WEI*
Affiliation:
School of Biomedical Information and Engineering, Hainan Medical University, Haikou 571199, PR China
Rights & Permissions [Opens in a new window]

Abstract

We derive a q-supercongruence modulo the third power of a cyclotomic polynomial with the help of Guo and Zudilin’s method of creative microscoping [‘A q-microscope for supercongruences’, Adv. Math. 346 (2019), 329–358] and the q-Dixon formula. As consequences, we give several supercongruences including

$$ \begin{align*}\sum_{k=0}^{(p-2)/3}\frac{(\frac{2}{3})_k^3}{(1)_k^3}\equiv\frac{p}{2}\frac{(1)_{(p-2)/3}}{(\frac{4}{3})_{(p-2)/3}}\pmod{p^3},\end{align*} $$

where p is a prime with $p\equiv 5\pmod {6}$ .

Type
Research Article
Copyright
© The Author(s), 2022. Published by Cambridge University Press on behalf of Australian Mathematical Publishing Association Inc.

1 Introduction

For any complex variable x, define the shifted-factorial by

$$ \begin{align*}(x)_{0}=1\quad \text{and}\quad (x)_{n} =x(x+1)\cdots(x+n-1)\quad \text{for } n\in\mathbb{Z}^{+},\end{align*} $$

and let $\Gamma _{p}(x)$ denote the p-adic Gamma function. Throughout the paper, p denotes an odd prime. In 1997, Van Hamme [Reference Van Hamme, Schikhof, Perez-Garcia and Kakol9, (H.2)] proved that

(1.1) $$ \begin{align} \sum_{k=0}^{(p-1)/2}\frac{(\frac{1}{2})_k^3}{(1)_k^3}\equiv \begin{cases} \displaystyle -\Gamma_p\biggl(\frac{1}{4}\biggr)^4 \pmod{p^2} &\text{if } p\equiv 1\pmod 4,\\[3pt] 0\pmod{p^2} &\text{if } p\equiv 3\pmod 4. \end{cases} \end{align} $$

In 2016, Long and Ramakrishna [Reference Long and Ramakrishna6] gave an extension of (1.1):

(1.2) $$ \begin{align} \sum_{k=0}^{(p-1)/2}\frac{(\frac{1}{2})_k^3}{(1)_k^3}\equiv \begin{cases} \displaystyle -\Gamma_p\biggl(\frac{1}{4}\biggr)^4 \pmod{p^3} &\text{if } p\equiv 1\pmod 4,\\[8pt] \displaystyle -\frac{p^2}{16}\Gamma_p\biggl(\frac{1}{4}\biggr)^4\pmod{p^3} &\text{if } p\equiv 3\pmod 4. \end{cases} \end{align} $$

In the same year, Deines et al. [Reference Deines, Fuselier, Long, Swisher, Tu and Lauter1] discovered the nice supercongruence: for $p\equiv {1}\pmod {6}$ ,

$$ \begin{align*}\sum_{k=0}^{p-1}\frac{(\frac{2}{3})_k^3}{(1)_k^3}\equiv-\Gamma_{p}\biggl(\frac{1}{3}\biggr)^3\pmod{p^3}.\end{align*} $$

Several years later, Mao and Pan [Reference Mao and Pan7] (see also Sun [Reference Sun8, Theorem 1.3]) found a result similar to (1.1): for $p\equiv 1\pmod {4}$ ,

(1.3) $$ \begin{align} \sum_{k=0}^{(p+1)/2}\frac{(-\frac{1}{2})_k^3}{(1)_k^3}\equiv0\pmod{p^2}. \end{align} $$

For any complex numbers x and q, define the q-shifted factorial by

$$ \begin{align*} (x;q)_{0}=1\quad\text{and}\quad (x;q)_n=(1-x)(1-xq)\cdots(1-xq^{n-1})\quad \text{for } n\in\mathbb{Z}^{+}. \end{align*} $$

For simplicity, we also adopt the compact notation

$$ \begin{align*} (x_1,x_2,\ldots,x_m;q)_{n}=(x_1;q)_{n}(x_2;q)_{n}\cdots(x_m;q)_{n}, \end{align*} $$

where $m\in \mathbb {Z}^{+}$ and $n\in \mathbb {Z}^{+}\cup \{0,\infty \}.$ Let $[n]=(1-q^n)/(1-q)$ be the q-integer and let $\Phi _n(q)$ stand for the nth cyclotomic polynomial in q:

$$ \begin{align*} \Phi_n(q)=\prod_{\substack{1\leqslant k\leqslant n\\[3pt] \gcd(k,n)=1}}(q-\zeta^k), \end{align*} $$

where $\zeta $ is a primitive nth root of unity. Recently, Wei [Reference Wei11] and Wang [Reference Wang10] established q-analogues of (1.2) for the first case: if $n\equiv 1\pmod 4$ , then modulo $\Phi _n(q)^3$ ,

$$ \begin{align*} \sum_{k=0}^{(n-1)/2}\frac{(q;q^2)_k^2(q^2;q^4)_k}{(q^2;q^2)_k^2(q^4;q^4)_k}q^{2k} & \equiv q^{(n-1)/2}\frac{(q^2;q^4)_{(n-1)/4}^2}{(q^4;q^4)_{(n-1)/4}^2}\bigg\{1+2[n]^2\sum_{i=1}^{(n-1)/4}\frac{q^{4i-2}}{[4i-2]^2}\bigg\},\\[3pt] \sum_{k=0}^{(n-1)/2}\frac{(q;q^2)_k^2(q^{2};q^4)_k}{(q^2;q^2)_k^2(q^4;q^4)_k}q^{2k} & \equiv[n]\frac{(q^3;q^4)_{(n-1)/2}}{(q^5;q^4)_{(n-1)/2}} \\[3pt] &\quad+ [n]^3\sum_{k=0}^{(n-3)/2}\frac{(1+q^{2k+1})(q^3;q^4)_k}{[2k+1]^2(q^5;q^4)_k}q^{2k+1}. \end{align*} $$

Guo and Zudilin [Reference Guo and Zudilin5] and Guo [Reference Guo3] gave q-analogues of (1.2) for the second case: if $n\equiv 3\pmod 4$ , then

(1.4) $$ \begin{align} \sum_{k=0}^{(n-1)/2}\frac{1+q^{1+4k}}{1+q}\frac{(q^{2};q^4)_k^3}{(q^4;q^4)_k^3}q^{k} & \equiv [n]_{q^2}\frac{(q^3;q^4)_{(n-1)/2}}{(q^5;q^4)_{(n-1)/2}}q^{(1-n)/2}\pmod{\Phi_n(q)^3}, \notag\\[2mm] \sum_{k=0}^{(n-1)/2}\frac{(q;q^2)_k^2(q^{2};q^4)_k}{(q^2;q^2)_k^2(q^4;q^4)_k}q^{2k} & \equiv [n]\frac{(q^3;q^4)_{(n-1)/2}}{(q^5;q^4)_{(n-1)/2}}\pmod{\Phi_n(q)^3}. \end{align} $$

Guo and Zudilin [Reference Guo and Zudilin5] also found the q-supercongruence: for any positive integer $n>1$ with $n\equiv 1\pmod 4$ ,

(1.5) $$ \begin{align} \sum_{k=0}^{(n+1)/2}\frac{1+q^{4k-1}}{1+q}\frac{(q^{-2};q^4)_k^3}{(q^4;q^4)_k^3}q^{7k} \equiv [n]_{q^2}\frac{(q;q^4)_{(n-1)/2}}{(q^5;q^4)_{(n-1)/2}}q^{(n-3)/2}\pmod{\Phi_n(q)^3}. \end{align} $$

Setting $n=p$ and then letting $q\to 1$ in (1.5), they obtain the extension of (1.3): for $p\equiv 1\pmod 4$ ,

$$ \begin{align*} \sum_{k=0}^{(p+1)/2}\frac{(-\frac{1}{2})_k^3}{k!^3}\equiv p\frac{(\frac{1}{4})_{(p-1)/2}}{(\frac{7}{4})_{(p-1)/2}}\pmod{p^3}. \end{align*} $$

Motivated by the results just mentioned, we shall establish the following theorem.

Theorem 1.1. Let $n, d$ be positive integers such that $n-dn+2d\leq r\leq n+d$ , $\gcd (n, d) = 1$ and $n\equiv r\pmod {2d}$ . Then

$$ \begin{align*} &\sum_{k=0}^{(n-r+d)/d}\frac{1+q^{r-d+2dk}}{1+q^{r-d}}\frac{(q^{2r-2d};q^{2d})_k^3}{(q^{2d};q^{2d})_k^3}q^{(5d-3r)k} \\[3pt] &\quad\equiv \frac{1-q^{2n}}{1-q^{2r-2d}}\frac{(q^{3r-3d};q^{2d})_{(n-r+d)/d}}{(q^{r+d};q^{2d})_{(n-r+d)/d}}q^{(d-r)(n-r+d)/d}\pmod{\Phi_n(q)^3}. \end{align*} $$

Obviously, the $d=2, r=3$ case of Theorem 1.1 is exactly (1.4). When $d=2, r=1$ , Theorem 1.1 reduces to (1.5). Taking $n=p$ and then letting $q\to 1$ in Theorem 1.1 gives the following supercongruence.

Proposition 1.2. Let p be an odd prime and let d be a positive integer such that $p-dp+2d\leq r\leq p+d$ and $p\equiv r\pmod {2d}$ . Then

$$ \begin{align*} \sum_{k=0}^{(p-r+d)/d}\frac{(\frac{r-d}{d})_k^3}{(1)_k^3}\equiv \frac{p}{r-d}\frac{(\frac{3r-3d}{2d})_{(p-r+d)/d}}{(\frac{r+d}{2d})_{(p-r+d)/d}}\pmod{p^3}. \end{align*} $$

Specialising the parameters d and r, Proposition 1.2 can produce many concrete supercongruences. Six of these are given in the following corollaries.

Corollary 1.3. Let p be a prime with $p\equiv 1\pmod {6}$ . Then

$$ \begin{align*} \sum_{k=0}^{(p+2)/3}\frac{(-\frac{2}{3})_k^3}{(1)_k^3}\equiv 0\pmod{p^3}. \end{align*} $$

Proof. Take $d=3, r=1$ in Proposition 1.2.

Corollary 1.4. Let p be a prime with $p\equiv 5\pmod {6}$ . Then

$$ \begin{align*} \sum_{k=0}^{(p-2)/3}\frac{(\frac{2}{3})_k^3}{(1)_k^3}\equiv \frac{p}{2}\frac{(1)_{(p-2)/3}}{(\frac{4}{3})_{(p-2)/3}}\pmod{p^3}. \end{align*} $$

Proof. Take $d=3, r=5$ in Proposition 1.2.

Corollary 1.5. Let p be a prime with $p\equiv 1\pmod {8}$ . Then

$$ \begin{align*} \sum_{k=0}^{(p+3)/4}\frac{(-\frac{3}{4})_k^3}{(1)_k^3}\equiv -\frac{p}{3}\frac{(-\frac{9}{8})_{(p+3)/4}}{(\frac{5}{8})_{(p+3)/4}}\pmod{p^3}. \end{align*} $$

Proof. Take $d=4, r=1$ in Proposition 1.2.

Corollary 1.6. Let p be a prime with $p\equiv 3\pmod {8}$ . Then

$$ \begin{align*} \sum_{k=0}^{(p+1)/4}\frac{(-\frac{1}{4})_k^3}{(1)_k^3}\equiv -p\frac{(-\frac{3}{8})_{(p+1)/4}}{(\frac{7}{8})_{(p+1)/4}}\pmod{p^3}. \end{align*} $$

Proof. Take $d=4, r=3$ in Proposition 1.2.

Corollary 1.7. Let p be a prime with $p\equiv 5\pmod {8}$ . Then

$$ \begin{align*} \sum_{k=0}^{(p-1)/4}\frac{(\frac{1}{4})_k^3}{(1)_k^3}\equiv p\frac{(\frac{3}{8})_{(p-1)/4}}{(\frac{9}{8})_{(p-1)/4}}\pmod{p^3}. \end{align*} $$

Proof. Take $d=4, r=5$ in Proposition 1.2.

Corollary 1.8. Let p be a prime with $p\equiv 7\pmod {8}$ . Then

$$ \begin{align*} \sum_{k=0}^{(p-3)/4}\frac{(\frac{3}{4})_k^3}{(1)_k^3}\equiv \frac{p}{3}\frac{(\frac{9}{8})_{(p-3)/4}}{(\frac{11}{8})_{(p-3)/4}}\pmod{p^3}. \end{align*} $$

Proof. Take $d=4, r=7$ in Proposition 1.2.

We shall prove Theorem 1.1 in the next section by means of the creative microscoping method recently introduced by Guo and Zudilin [Reference Guo and Zudilin4].

2 Proof of Theorem 1.1

Following Gasper and Rahman [Reference Gasper and Rahman2], define the basic hypergeometric series by

$$ \begin{align*} _{r+1}\phi_{r}\left[\begin{array}{c} a_1,a_2,\ldots,a_{r+1}\\[3pt] b_1,b_2,\ldots,b_{r} \end{array};q,\, z \right] =\sum_{k=0}^{\infty}\frac{(a_1,a_2,\ldots, a_{r+1};q)_k} {(q,b_1,b_2,\ldots,b_{r};q)_k}z^k. \end{align*} $$

To prove Theorem 1.1, we require the q-Dixon formula:

(2.1) $$ \begin{align} _{4}\phi_{3}\!\left[\begin{array}{c} a, \, -qa^{{1}/{2}}, \, b, \, c \\[3pt] -a^{{1}/{2}}, \, aq/b, \, aq/c \end{array};q,\,\frac{qa^{{1}/{2}}}{bc} \right] =\frac{(aq,aq/bc,qa^{{1}/{2}}/b,qa^{{1}/{2}}/c;q)_{\infty}}{(aq/b,aq/c,qa^{{1}/{2}},qa^{{1}/{2}}/bc;q)_{\infty}}, \end{align} $$

where $|qa^{{1}/{2}}/bc|<1$ .

Proof of Theorem 1.1.

Setting $a=q^{-1-2n}$ in (2.1), we obtain

$$ \begin{align*} _{4}\phi_{3}\!\left[\begin{array}{c} q^{-1-2n},\, -q^{{1}/{2}-n},\, b,\, c \\[3pt] -q^{-{1}/{2}-n},\, q^{-2n}/b,\, q^{-2n}/c \end{array};q,\,\frac{q^{{1}/{2}-n}}{bc} \right] =0. \end{align*} $$

Performing the simultaneous replacements $n\mapsto (n-r)/2d$ , $q\mapsto q^{2d}$ , $b\mapsto bq^{2r-2d}$ , $c\mapsto q^{2r-2d}/b$ in the above identity, we get

$$ \begin{align*} _{4}\phi_{3}\!\left[\begin{array}{c} q^{2r-2d-2n},\, -q^{r+d-n},\, bq^{2r-2d},\, q^{2r-2d}/b \\[6pt] -q^{r-d-n},\, q^{2d-2n}/b,\, bq^{2d-2n} \end{array};q^{2d},\,q^{5d-3r-n} \right] =0. \end{align*} $$

This gives the following congruence: modulo $(a^2-q^{2n})$ ,

(2.2) $$ \begin{align} \sum_{k=0}^{(n-r+d)/d}\frac{1+q^{r-d+2dk}/a}{1+q^{r-d}/a}\frac{(q^{2r-2d}/a^2,bq^{2r-2d},q^{2r-2d}/b;q^{2d})_k} {(q^{2d},q^{2d}/a^2b,q^{2d}b/a^2;q^{2d})_k}\bigg(\frac{q^{5d-3r}}{a}\bigg)^k \equiv 0. \end{align} $$

However, taking $c=q^{-1-2n}$ in (2.1), we obtain

$$ \begin{align*} _{4}\phi_{3}\!\left[\begin{array}{c} a,\, -qa^{{1}/{2}},\, b,\, q^{-1-2n} \\[6pt] -a^{{1}/{2}},\, aq/b,\, aq^{2+2n} \end{array};q,\,\frac{q^{2+2n}a^{{1}/{2}}}{b} \right] =\frac{(aq,qa^{{1}/{2}}/b;q)_{1+2n}}{(aq/b,qa^{{1}/{2}};q)_{1+2n}}. \end{align*} $$

Employing the substitutions $n\mapsto (n-r)/2d$ , $q\mapsto q^{2d}$ , $a\mapsto q^{2r-2d}/a^2$ , $b\mapsto q^{2r-2d+2n}$ , we arrive at

$$ \begin{align*} &_{4}\phi_{3}\!\left[\begin{array}{c} q^{2r-2d}/a^2,\, -q^{r+d}/a,\, q^{2r-2d+2n},\, q^{2r-2d-2n} \\[6pt] -q^{r-d}/a,\, q^{2d-2n}/a^2,\, q^{2d+2n}/a^2 \end{array};q^{2d},\,\frac{q^{5d-3r}}{a} \right]\\[2mm] &\quad=(aq^{d-r})^{(n-r+d)/d}\frac{(q^{2r}/a^2,aq^{3r-3d};q^{2d})_{(n-r+d)/d}}{(q^{r+d}/a,a^2q^{2r-2d};q)_{(n-r+d)/d}}. \end{align*} $$

This gives the following congruence: modulo $(b-q^{2n})(1-bq^{2n})$ ,

(2.3) $$ \begin{align} &\sum_{k=0}^{(n-r+d)/d}\frac{1+q^{r-d+2dk}/a}{1+q^{r-d}/a}\frac{(q^{2r-2d}/a^2,bq^{2r-2d},q^{2r-2d}/b;q^{2d})_k} {(q^{2d},q^{2d}/a^2b,q^{2d}b/a^2;q^{2d})_k}\bigg(\frac{q^{5d-3r}}{a}\bigg)^k\notag\\[2pt] &\quad\equiv (aq^{d-r})^{(n-r+d)/d}\frac{(q^{2r}/a^2,aq^{3r-3d};q^{2d})_{(n-r+d)/d}}{(q^{r+d}/a,a^2q^{2r-2d};q)_{(n-r+d)/d}}. \end{align} $$

Note that the right-hand side of (2.2) can also be written as that of (2.3), since $(q^{2r}/a^2,aq^{3r-3d};q^{2d})_{(n-r+d)/d}$ contains the factor $a^2-q^{2n}$ . It is clear that the polynomials $(a^2-q^{2n})$ and $(b-q^{2n})(1-bq^{2n})$ are relatively prime. Therefore, from (2.2) and (2.3) we deduce that, modulo $(a^2-q^{2n})(b-q^{2n})(1-bq^{2n})$ ,

(2.4) $$ \begin{align} &\sum_{k=0}^{(n-r+d)/d}\frac{1+q^{r-d+2dk}/a}{1+q^{r-d}/a}\frac{(q^{2r-2d}/a^2,bq^{2r-2d},q^{2r-2d}/b;q^{2d})_k} {(q^{2d},q^{2d}/a^2b,q^{2d}b/a^2;q^{2d})_k}\bigg(\frac{q^{5d-3r}}{a}\bigg)^k\notag\\[2pt] &\quad\equiv (aq^{d-r})^{(n-r+d)/d}\frac{(q^{2r}/a^2,aq^{3r-3d};q^{2d})_{(n-r+d)/d}}{(q^{r+d}/a,a^2q^{2r-2d};q)_{(n-r+d)/d}}. \end{align} $$

Letting $a {\kern2pt\to\kern2pt} 1$ , $b{\kern2pt\to\kern2pt} 1$ in (2.4), we are led to the q-supercongruence in Theorem 1.1.

3 Two open problems

Numerical calculations indicate the following two open problems related to Corollaries 1.3 and 1.5.

Conjecture 3.1. Let p be a prime with $p\equiv 1\pmod {6}$ and let s be a positive integer. Then

$$ \begin{align*} \sum_{k=0}^{(p^s+2)/3}\frac{(-\frac{2}{3})_k^3}{(1)_k^3}\equiv 0\pmod{p^{3s}}. \end{align*} $$

Conjecture 3.2. Let p be a prime with $p\equiv 1\pmod {8}$ and let s be a positive integer. Then

$$ \begin{align*} \sum_{k=0}^{(p^s+3)/4}\frac{(-\frac{3}{4})_k^3}{(1)_k^3}\equiv -\frac{p^s}{3}\frac{(-\frac{9}{8})_{(p^s+3)/4}}{(\frac{5}{8})_{(p^s+3)/4}}\pmod{p^{s+2}}. \end{align*} $$

Acknowledgement

The author is grateful to the reviewer for a careful reading and valuable comments.

Footnotes

This work is supported by the National Natural Science Foundation of China (No. 12071103).

References

Deines, A., Fuselier, J. G., Long, L., Swisher, H. and Tu, F.-T., ‘Hypergeometric series, truncated hypergeometric series, and Gaussian hypergeometric functions’, in: Directions in Number Theory, (ed. Lauter, K.), Association for Women in Mathematics Series, 3 (Springer, New York, 2016), 125159.CrossRefGoogle Scholar
Gasper, G. and Rahman, M., Basic Hypergeometric Series, 2nd edn (Cambridge University Press, Cambridge, 2004).CrossRefGoogle Scholar
Guo, V. J. W., ‘A further $q$ -analogue of Van Hamme’s (H.2) supercongruence for primes $p\equiv 3\left(\mathrm{mod}\ 4\right)$ ’, Int. J. Number Theory 17 (2021), 12011206.CrossRefGoogle Scholar
Guo, V. J. W. and Zudilin, W., ‘A $q$ -microscope for supercongruences’, Adv. Math. 346 (2019), 329358.CrossRefGoogle Scholar
Guo, V. J. W. and Zudilin, W., ‘A common $q$ -analogue of two supercongruences’, Results Math. 75 (2020), Article no. 46.CrossRefGoogle Scholar
Long, L. and Ramakrishna, R., ‘Some supercongruences occurring in truncated hypergeometric series’, Adv. Math. 290 (2016), 773808.CrossRefGoogle Scholar
Mao, G.-S. and Pan, H., ‘On the divisibility of some truncated hypergeometric series’, Acta Arith. 195 (2020), 199206.CrossRefGoogle Scholar
Sun, Z.-W., ‘On sums of Apéry polynomials and related congruences’, J. Number Theory 132 (2012), 26732690.CrossRefGoogle Scholar
Van Hamme, L., ‘Some conjectures concerning partial sums of generalized hypergeometric series’, in: $p$ -Adic Functional Analysis (Nijmegen, 1996) (eds. Schikhof, W. H., Perez-Garcia, C. and Kakol, J.), Lecture Notes in Pure and Applied Mathematics , 192 (Dekker, New York, 1997), 223236.Google Scholar
Wang, C., ‘A new $q$ -extension of the (H.2) congruence of Van Hamme for primes $p\equiv 1\left(\mathrm{mod}\ 4\right)$ ’, Results Math. 76 (2021), Article no. 205.CrossRefGoogle Scholar
Wei, C., ‘A further $q$ -analogue of Van Hamme’s (H.2) supercongruence for any prime $p\equiv 1 \left(\mathrm{mod}\ 4\right)$ ’, Results Math. 76 (2021), Article no. 92.CrossRefGoogle Scholar